Early postnatal nutrition after preterm birth and cardiometabolic risk factors in young adulthood - Suikkanen Julia; Matinolli Hanna-Maria; Eriksson Johan G; Järvenpää Anna-Liisa; Andersson Sture; Kajantie Eero; Hovi Petteri (My University, 2025)
Adults born preterm at very low birthweight (VLBW; <1500 g) have a non-optimal cardiometabolic risk factor profile. Since higher protein intake during the first weeks of life predicted a healthier body composition in adulthood in our previous studies, we hypothesized that it would also predict a favorable cardiometabolic profile.
STUDY DESIGN:
The Helsinki Study of VLBW Adults includes 166 VLBW and preterm infants born between 1978 and 1985. We collected postnatal nutrition data among 125 unimpaired subjects, who attended two study visits at the mean ages of 22.5 and 25.1 years. We evaluated the effects of energy and macronutrient intakes during the first three 3-week periods of life on key cardiometabolic risk factors with multiple linear regression models. We also report results adjusted for prenatal, postnatal and adult characteristics.
RESULTS:
Macronutrient and energy intakes were not associated with blood pressure, heart rate, or lipid levels in adulthood. Intakes were neither associated with fasting glucose or most other markers of glucose metabolism. An exception was that the first-three-weeks-of-life intakes predicted higher fasting insulin levels: 1 g/kg/day higher protein intake by 37.6% (95% CI: 8.0%, 75.2%), and 10 kcal/kg/day higher energy intake by 8.6% (2.6%, 14.9%), when adjusted for sex and age. These early intakes similarly predicted the adult homeostasis model assessment index. Further adjustments strengthened these findings.
CONCLUSIONS:
Among VLBW infants with relatively low early energy intake, early macronutrient and energy intakes were unrelated to blood pressure, lipid levels and intravenous glucose tolerance test results. Contrary to our hypothesis, a higher macronutrient intake during the first three weeks of life predicted higher fasting insulin concentration in young adulthood.